Activity of Sanguinarine against Candida albicans Biofilms - Zhong, Hua (Antimicrob Agents Chemother, 2017)
Candida albicans biofilms show resistance to many clinical antifungal agents and play a considerable contributing role in the process of C. albicans infections. New antifungal agents against C. albicans biofilms are sorely needed. The aim of this study was to evaluate sanguinarine (SAN) for its activity against Candida albicans biofilms and explore the underlying mechanism. The MIC(50) of SAN was 3.2 μg/ml, while ≥0.8 μg/ml of SAN could suppress C. albicans biofilms. Further study revealed that ≥0.8 μg/ml of SAN could decrease cellular surface hydrophobicity (CSH) and inhibited hypha formation. Real-time reverse transcription-PCR (RT-PCR) results indicated that the exposure of C. albicans to SAN suppressed the expression of some adhesion- and hypha-specific/essential genes related to the cyclic AMP (cAMP) pathway, including ALS3, HWP1, ECE1, HGC1, and CYR1. Consistently, the endogenous cAMP level of C. albicans was downregulated after SAN treatment, and the addition of cAMP rescued the SAN-induced filamentation defect. In addition, SAN showed relatively low toxicity to human umbilical vein endothelial cells, the 50% inhibitory concentration (IC(50)) being 7.8 μg/ml. Collectively, the results show that SAN exhibits strong activity against C. albicans biofilms, and the activity was associated with its inhibitory effect on adhesion and hypha formation due to cAMP pathway suppression.